Green synthesis of zinc oxide nanoparticles toward highly efficient photocatalysis and antibacterial application - Nhu, Vo Thi Thu; Dat, Nguyen Duy; Tam, Le-Minh; Phuong, Nguyen Hoang (Beilstein Journal of Nanotechnology, 2022)
Zinc oxide nanoparticles (ZnO NPs) were successfully synthesized by a green method using rosin and zinc chloride as salt precursors. The phase structure, morphology, and particle size of ZnO were determined by X-ray powder diffraction, field emission scanning electron microscopy, and high-resolution transmission electron microscopy. The fabricated ZnO NP samples are crystalline with a grain size of 30–100 nm. The ZnO NPs were used as catalysts for the photodegradation of methylene blue (MB) and methyl orange (MO) under visible and UV light. The results indicate that the prepared ZnO material excellently removed MB and MO (cinitial = 10 mg/L) with efficiencies of 100% and 82.78%, respectively, after 210 min under UV radiation with a ZnO NP dose of 2 g/L. The photocatalyst activity of the synthesized material was also tested under visible light radiation with the same conditions; however, it achieved lower efficiencies. In addition, ZnO NPs were also tested regarding their antibacterial activity, and the results showed that the prepared ZnO samples had the highest (i.e., 100%) antibacterial efficiency against E. coli.
Keywords: green synthesis; methylene blue; methyl orange; rosin; ZnO nanoparticles